EVALUACIÓN DE RESIDUALIDAD DE DIFERENTES FUNGICIDAS PARA EL CONTROL DE LA SIGATOKA NEGRA (Mycosphaerella fijiensis) EN EL CULTIVO DE BANANO (Musa paradisiaca) - Chalco Valdez, Yerson Damian (2023)
The objective of the research is to evaluate the residuality of different chemical groups of fungicides for the control of the pathogenic agent Mycosphaerella fijiensis in banana crops. This was carried out at the Banana Research Field (CIB) under an agreement with BASF Ecuador, using four treatments and four subtreatments or combinations for each treatment, which included a mixture of two fungicides for the control of sigatoka. A randomized complete block design (RCBD) was applied, consisting of 5 treatments and 4 replicates.